Charlie Dillon: capstone - Dillon, Charlie, artist (Colorado State University. Libraries, 2022)
The artist's statement: My paintings are a love letter to my friends and to the world around me, written in bold colors and intimate scenes. Through the permanency of paintings, I hope to make solid these snapshots of temporary moments, and with it capture something fleeting and usually lost to our bloated phone camera rolls or foggy memories. I am fascinated by the role that mundane technologies act to mediate, disrupt, or otherwise alter moments in our memories, whether that be something more direct like a phone camera recording a scene, or more indirect, like being on Twitter instead of being emotionally present in one’s life. Growing up with technology as both a barrier and a condenser of space, I’m interested in this mediation in connection to time. I aim to explore what power we give moments by tactilely and visually considering them with paint, through these forms of attention. With this, my practice involves collecting images from these quick moments with little or no staging. Currently, I’m excited by building compositions and color palettes to convey the everyday chaos and intimacy of my early 20s, which feels like a second coming-of-age, or an Adolescence 2.0. These paintings convey this transitory period; the disorder of it through partially obscured figures and the uncertainty through dancing around the canvas with brushstrokes and colors. Within this, I’m interested both in the cues that demonstrate individually who a person is; such as fashion, mannerisms, expressions, and gestures, while also being interested in more formal elements and building compositions structurally and with colors that convey universalities and common feelings or moods through these small, specific moments. Through these pieces, I am considering the reverence and power given to mundane moments by deliberately painting them for hours.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting